Space Maintainer Treatment In Premature Loss Deciduous Tooth - Rey Bintang Pamungkas; Jeffrey . (Maranatha Christian University, 2020)
Abstract. Introduction: The deciduous tooth period is an important period in child development. Premature loss of deciduous teeth is defined as the loss of deciduous teeth before they approach the eruption of permanent teeth. The prevalance of premature loss offered in several studies obtained was between 4.3% and 42.6%. Method: An 10 years-old-boy accompanied by her mother came to RSGMP Unjani, complaints of lower right nack teeth missing because they have to extracted since 3 mouth ago. Tooth have been extracted because of caries. Result: Result of clinical examination was found premature loss teeth 75, 74, and 85. The space in Moyers analysis was +0.2 mm in region 3 and +0.1 mm in region 4. Patient was treated with a fungsional removable-space-maintainer on teeth 75, 74, and 85. Conclusion: The results of premature loss is excess space in the arch, so to prevent further occlusion abnormalities in child’s growth and development process, we need a special appliance that is used to protect the space due to premature loss of deciduous teeth. Keywords: Premature loss, space maintainer, deciduous teeth